PEMASARAN PARIWISATA DIGITAL OLEH PEMERINTAH KOTA SABANG - Christina Indriani Sianipar; Liyushiana Liyushiana (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2019)
The rapid development of technology at this time so that the manual system has almost been completely abandoned. The development of this technology is also felt in marketing and distributing information about a tourist destination. Government organizations are no less affected by the rapid development of technology in marketing tourist destinations. The trend is no longer focused on the distribution of brochures or leaflets that are printed physically, but by using digital media. The purpose of this study was carried out, to see how the Tourism and Culture Office of Sabang City, in marketing tourism destinations using digital media, made use of several media such as, websites, youtube, social media (Facebook, Instagram, Twitter) in their marketing. The research instrument used was an interview technique, which was given to the government and a questionnaire given to tourists visiting tourist objects in Sabang. Therefore the title was raised as